ORIENTASI USHUL FIQH (Definisi, Objek, Sejarah, Latar belakang, Tujuan, Aliran, Perbedaan Ushul Fiqh dan Qowaid Fiqhiyah.) - Mutia Marwa; Nurzakia Syahra; Astrid Ananda (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This article explains that Usul al-Fiqh is one of the fundamental disciplines in the treasury of Islamic knowledge that serves as a methodology for exploring sharia law. The study of the orientation of ushul al-fiqh covers various aspects, from its definition, object, historical development, to the objectives behind the birth of this discipline. Usul al-fiqh is defined as a set of rules and methods used to understand sharia arguments, thereby generating practical law (fiqh). The object of study does not only revolve around the arguments of the Qur'an, hadith, ijma', and qiyas, but also discusses the method of systematic istinbath of law. The history of ushul al-fiqh shows significant developments from the time of the companions to the codification by classical scholars such as Imam Shafi'i, which then gave rise to various schools of thought and methodological approaches. The main objective of ushul al-fiqh is to maintain the consistency of legal determination so that it remains in accordance with the maqasid al-sharia, while also providing flexibility in dealing with social dynamics. Furthermore, it is important to distinguish between ushul fiqh and qawaid fiqh. Ushul fiqh serves as a methodology for istinbath (determination of the law), while qawaid fiqh is a general and applicable practical principle in furu' (legal issues). Therefore, a comprehensive understanding of the orientation of ushul fiqh provides a crucial contribution to building an Islamic legal system that is relevant, adaptive, and remains grounded in the basic principles of sharia.